124 Impact of contrast-induced nephropathy upon short and long-term outcomes of patients with ST-segment elevation myocardial infarction undergoing primary percutaneous coronary intervention. (16th May 2012) - Gallagher, Sean; Hassan, S; Jones, D A; Lovell, M J; Ahktar, A; Kapur, A; Knight, C; Mathur, A; Yaqoob, M M; Wragg, A
Abstract : Introduction: Contrast induced nephropathy (CIN) is associated with adverse clinical outcomes, including prolonged hospitalisation and increased morbidity and mortality following elective invasive cardiac procedures. The impact of CIN following primary PCI (PPCI) for ST segment elevation MI (STEMI) remains poorly defined. Aim: To investigate the long-term prognostic implications of CIN following PPCI for STEMI. Methods: This is a retrospective observational registry study. Data were available upon 2224 patients undergoing PPCI for STEMI at a tertiary Cardiac centre between October 2003 and May 2010. CIN was defined as an increase in serum creatinine (>25% or 44.2 mmol/l) within 2 days of PPCI. The primary outcome measure was all-cause mortality determined via Office of National Statistics data. Results: CIN was observed in 317 patients (14.3%). Patients with CIN were older (69.3 vs 62.7, p<0.0001), more likely to be female (30.0% vs 22.6% p=0.004), had more vascular risk factors (including diabetes, hypertension and chronic kidney disease), had more previous MIs (17.7% vs 11.7%, p=0.003), more multivessel CAD (55.2% vs 40.6%, p<0.0001), and more LV dysfunction (52.1% vs 32.1%, p<0.0001) (Abstract 124 table 1 ). Length of hospital stay (5 vs 2 days, p<0.0001), 30-day mortality (16.4% vs 2.0%, p<0.0001) and 3-year mortality (22.4% vs 5.0%, Log rank p<0.0001) (Abstract 124 figure 1 ) was worse in patients with CIN. CIN was an important independent predictor of all cause mortality (HR 2.71, CI 1.97 to 3.75). Other independent predictors of mortality included age>75 years (HR 1.81, CI 1.28 to 2.57), eGFR <60 mls/min (HR 2.36, CI 1.69 to 3.31), cardiogenic shock (HR 3.98, CI 2.76 to 5.73), LV dysfunction (HR 1.82, CI 1.34 to 2.48) and multivessel CAD (HR 1.59, CI 1.15 to 2.20). Conclusion: CIN following PPCI for STEMI was associated with increased short and long-term mortality and increased length of hospital stay. Better strategies are needed to prevent CIN in high risk STEMI patients.